Information and Communication Technology in Online Learning Process - Y Sutisnawati; I L Ramdani; A M Fitriyani; I Ariska; A A Rafdhi (International Journal of Education, Information Technology, and Others, 2021)
This study aims to analyze Information and Communication Technology (ICT) in the online learning process. The method used to meet the needs of analysis was the descriptive method with a qualitative approach. This study indicates the use of information and communication technology has an important role in the implementation of online learning. This learning process can run well with the existence of information and communication technology that has developed quite rapidly, coupled with applications that support the implementation of online learning, such as Zoom meetings that provide easy access and have many advantages and other information media. This paper aims to improve the quality of learning, expand access to learning, visualize abstract ideas, present learning material to be more attractive, and make it easier for us to find information; with this, students can learn easily and be done anytime and anywhere. This paper concludes that if information and communication technology (ICT) is well designed and developed and utilized according to the objectives and characteristics of an institution, the use of information and communication technology in learning will improve the quality of learning, both the process and the results.